2020
DOI: 10.3390/microorganisms8111636
|View full text |Cite
|
Sign up to set email alerts
|

The Mobile Colistin Resistance Gene, mcr-1.1, Is Carried on IncX4 Plasmids in Multidrug Resistant E. coli Isolated from Rainbow Trout Aquaculture

Abstract: Colistin, a last resort antibiotic, is important for controlling infections with carbapenem-resistant Enterobacteriaceae. The recent emergence of mobile-colistin-resistance (mcr) genes has threatened the effectiveness of colistin. Aquaculture is hypothesized to be a major contributor to the evolution and dissemination of mcr. However, data on mcr in aquaculture are limited. Here, the occurrence of mcr-1 was assessed in Rainbow Trout in Lebanon, a country with developing antimicrobial stewardship and an establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 65 publications
1
24
0
Order By: Relevance
“…A strength of our work refers to the identification of mcr-1 -bearing plasmids, which was almost absent from other studies in Lebanon ( Al-Mir et al, 2019 ; Hassan et al, 2020 ; Sourenian et al, 2020 ). With the single exception of one isolate where plasmid or chromosomal location was not clarified, all mcr-1 genes were detected on plasmids, mostly on IncX4 ( n = 36) but also on IncI2 ( n = 24).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…A strength of our work refers to the identification of mcr-1 -bearing plasmids, which was almost absent from other studies in Lebanon ( Al-Mir et al, 2019 ; Hassan et al, 2020 ; Sourenian et al, 2020 ). With the single exception of one isolate where plasmid or chromosomal location was not clarified, all mcr-1 genes were detected on plasmids, mostly on IncX4 ( n = 36) but also on IncI2 ( n = 24).…”
Section: Discussionmentioning
confidence: 98%
“…Finally, mcr-1 has also been reported in human clinical isolates in Lebanon that had been collected as early as 2011 ( Al-Mir et al, 2019 ). The plasmidic location of the mcr-1 gene has, however, rarely been investigated in those studies: it was found located on an IncX4 plasmid in human isolates and in a rainbow trout isolate, and on IncX4 and IncI2 in water isolates ( Al-Mir et al, 2019 ; Hassan et al, 2020 ; Sourenian et al, 2020 ). Likewise, data on the bacterial population structure hosting mcr-1 -mediated colistin-resistance remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…According to Hassan et al [ 112 ], a last resort antibiotic is colistin. Colistin is crucial for managing infections with carbapenem-resistant Enterobacteriaceae .…”
Section: Usage Of Antibiotics In Different Countries Of Eu Region mentioning
confidence: 99%
“…Food products are the number one exports in Lebanon, accounting for ~$1.7 billion in revenue [ 8 ]. However, Lebanon is currently struggling with wide-spread pollution, weakened infrastructure, political and civil unrest, and the most significant and debilitating economic crisis in its recent history [ 9 , 10 , 11 , 12 ]. Consequently, food safety and security issues in Lebanon have been on the rise with various cases of spoiled and expired food, fraud, and outbreaks that have received national attention [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are a plethora of factors that contribute to the status of food safety in Lebanon, including (1) absence of national baseline data on chemical and microbiological food contaminants, (2) insufficient scientific and technical expertise in the field, (3) scant financial support, (4) poor foodborne illness/outbreak surveillance, (5) inconsistent governmental oversight, transparency, and implementation and enforcement of policies and laws, (6) overlapping and conflicting jurisdictions of governmental agencies that oversee food safety, and (7) weak awareness of safety procedures in small food businesses [ 9 ]. Furthermore, there is limited support for academic research on the prevalence and properties of food contaminants and subsequent control mechanisms [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Taken together, these issues have left their mark on both the national economy and public health [ 33 ].…”
Section: Introductionmentioning
confidence: 99%